1999
DOI: 10.1097/00019606-199912000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lymphoid Cell Populations in Cytology Specimens Using Flow Cytometry and Polymerase Chain Reaction

Abstract: Differential diagnosis between lymphomas and reactive lymphoid proliferations often requires ancillary techniques and morphologic evaluation. Flow cytometry (FCM) and polymerase chain reaction (PCR) can aid the detection of monoclonal B-cell populations. In the present study, the sensitivity and specificity of these two methods in the study of cytology specimens were compared. Eighty-six cytologic specimens from 81 patients (lymph nodes, solid organs, and body cavities) were evaluated. These specimens were tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…This has been evidenced by studies showing that nonHodgkin lymphomas can be accurately diagnosed in cytologic specimens utilizing ancillary techniques such as immunocytochemistry and flow cytometry. 4,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In the REAL classification, ATLL belongs to the category of peripheral T-cell and natural killer cell neoplasms. Although several reports of peripheral Tcell lymphoma have been published in the cytology literature, [33][34][35][36][37] we are aware of only a single cytologic study of T-cell lymphoma in HTLV-1 positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…This has been evidenced by studies showing that nonHodgkin lymphomas can be accurately diagnosed in cytologic specimens utilizing ancillary techniques such as immunocytochemistry and flow cytometry. 4,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In the REAL classification, ATLL belongs to the category of peripheral T-cell and natural killer cell neoplasms. Although several reports of peripheral Tcell lymphoma have been published in the cytology literature, [33][34][35][36][37] we are aware of only a single cytologic study of T-cell lymphoma in HTLV-1 positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Normal ranges for the LCR differ between laboratories. A LCR threshold of two was reported to have a specificity of 92.3% and a sensitivity of 73.1% (98), while other studies proposed thresholds ranging from 2 to 6, with highest specificities and sensitivities around 70% (99)(100)(101)(102)(103)(104). This indicates that if, for example, a threshold of two is used, $10% of patients with a LCR above 2 are reported to have a monoclonal B-cell population, but do not have a B-cell lymphoma.…”
Section: Detection Of Monoclonal B-cell Populationsmentioning
confidence: 95%
“…In particular, IGH/TCR PCR can confirm FNC/FC diagnoses of lymphoma or assess polyclonality, adding clinical value to the FNC diagnoses of nodal and extranodal processes [40,54]. Mayall et al [55] maintain that, because of its high efficiency and short turnaround time, IGH/TCR PCR may replace FC on FNC samples, whereas Davidson et al [56] suggested that their combined use should be advisable because of a relatively high rate of monoclonality detection by PCR only. Maroto et al [4] stressed that IGH/TCR PCR enhances the LN FNC and FC diagnosis and cautioned on the risk of false positives and negatives by using a single primer pair PCR amplification over seminested methods.…”
Section: Pcr-based Assaysmentioning
confidence: 99%